Ancient Stratigraphy Preserving a Wet‐to‐Dry, Fluvio‐Lacustrine to Aeolian Transition Near Barth Crater, Arabia Terra, Mars. Issue 12 (23rd December 2019) - Day, Mackenzie; Edgett, Kenneth S.; Stumbaugh, Dominique
Abstract: Ancient lacustrine and aeolian sediments have been separately identified in a variety of locations on Mars. In this work, we interpret the depositional history of Barth crater and its surrounding area in Arabia Terra where exposed geologic units preserve a record of lacustrine and aeolian interaction. Aeolian sandstone in the study area overlies lacustrine strata and is interbedded with easily eroded interdune deposits. The aeolian sandstone preserves dune strata with structures that indicate paleo‐sediment transport toward the northwest. The aeolian unit also preserves a transition up‐section from separated barchan dunes to continuous transverse dunes, capturing the development of the ancient dune field from sediment limited to sediment rich. Inverted fluvial channels provide evidence that water was delivered to the area at the same time the dune field was present, providing a simple mechanism, via wetting and cementation, for aeolian strata preservation. This example of wet‐system aeolian accumulation preserves an upward drying sequence in the sedimentary record that may have been coincident with the widely hypothesized global climate transition. The terrains described in this work provide a framework for interpreting similar aeolian units in elsewhere on Mars, even where cross‐strata cannot be easily resolved. Plain Language Summary: Sedimentary rocks on Mars preserve evidence of the past environmental conditions on the planet. In and around Barth crater in Arabia Terra, Mars, the rock‐record preserves evidence of a wet‐to‐dry environmental transition much like the transition undergone at some point by the entire planet. Based on the surface expressions and characteristic structures in the sedimentary units, we interpret that Barth crater once hosted an ancient lake fed by rivers from the northeast. After the lake dried, dune fields formed on top of lake sediments, but intermittent re‐wetting of the region by flooding streams preserved some of the dune sands and deposited soft sediments between dunes. The lake, river, dune, and interdune deposits were later eroded by the wind, revealing the sedimentary structures (including crescent‐shaped forms) discussed in this work. Such patterns in deposition may reflect the wet‐to‐dry climatic transition that occurred on ancient Mars. Key Points: Curvilinear‐textured terrain in Arabia Terra preserves paleo‐dune strata Sedimentary units in Barth crater preserve a record of ancient interactions between fluvio‐lacustrine and aeolian deposition Ancient aeolian transport differed from modern transport by roughly 90° of azimuth